2022
DOI: 10.3389/fimmu.2022.1048204
|View full text |Cite
|
Sign up to set email alerts
|

Development of a polyamine gene expression score for predicting prognosis and treatment response in clear cell renal cell carcinoma

Abstract: BackgroundsPolyamine metabolism (PM) is closely related to the tumor microenvironment (TME) and is involved in antitumor immunity. Clear cell renal cell carcinoma (ccRCC) not only has high immunogenicity but also has significant metabolic changes. However, the role of PM in the immune microenvironment of ccRCC remains unclear. This study aimed to reveal the prognostic value of PM-related genes (PMRGs) expression in ccRCC and their correlation with the TME.MethodsThe expression levels PMRGs in different cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 154 publications
0
4
0
Order By: Relevance
“…High levels of polyamine metabolism are also a marker for poorer prognosis in clear cell renal carcinoma. Surprisingly, Chen et al found that clear cell renal carcinoma patients with high expression of polyamine-related genes show an increase in immune infiltrate but a poorer response to immunotherapies [ 177 ]. The authors discovered that high expression of polyamine-related genes was associated with increased Tregs in the TME and increased expression of T-cell exhaustion markers such as CTLA-4, TIGIT, and LAG3, indicating that while there may be more immune infiltrate in the TME, they may not be sensitive to immunotherapy due to immune escape [ 177 ].…”
Section: Preclinical and Clinical Relevance Of Polyamine-based Therap...mentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of polyamine metabolism are also a marker for poorer prognosis in clear cell renal carcinoma. Surprisingly, Chen et al found that clear cell renal carcinoma patients with high expression of polyamine-related genes show an increase in immune infiltrate but a poorer response to immunotherapies [ 177 ]. The authors discovered that high expression of polyamine-related genes was associated with increased Tregs in the TME and increased expression of T-cell exhaustion markers such as CTLA-4, TIGIT, and LAG3, indicating that while there may be more immune infiltrate in the TME, they may not be sensitive to immunotherapy due to immune escape [ 177 ].…”
Section: Preclinical and Clinical Relevance Of Polyamine-based Therap...mentioning
confidence: 99%
“…Surprisingly, Chen et al found that clear cell renal carcinoma patients with high expression of polyamine-related genes show an increase in immune infiltrate but a poorer response to immunotherapies [ 177 ]. The authors discovered that high expression of polyamine-related genes was associated with increased Tregs in the TME and increased expression of T-cell exhaustion markers such as CTLA-4, TIGIT, and LAG3, indicating that while there may be more immune infiltrate in the TME, they may not be sensitive to immunotherapy due to immune escape [ 177 ]. It is important to note that while gene expression of polyamine metabolism-related genes may be of prognostic value, it is not necessarily informative of polyamine levels in the tumor.…”
Section: Preclinical and Clinical Relevance Of Polyamine-based Therap...mentioning
confidence: 99%
“…Given that chemotherapy is still used as adjuvant therapy in the clinic, we conducted a search for potential drugs that can increase drug sensitivity in high-risk patients. This increase in sensitivity is due to changes in eRNA expression [24,25]. To evaluate chemotherapeutic sensitivity in the TCGA high-and low-risk sets, we utilized the "oncoPredict" R package.…”
Section: Twelve Potential Therapeutic Agents In the High-risk Groupmentioning
confidence: 99%
“…Afterwards, we visualized the variations in immune cells between cervical cancer and control samples using the packages limma, reshape2, and ggpubr. The main function of these packs is to correlate immune cells with their genes 15 .…”
Section: 5cibersort Immune Cell Composition Analysis Difference Analy...mentioning
confidence: 99%